PEMBAGIAN WARISAN ANAK DILUAR NIKAH DI KOTA LANGSA - Nawawi Abdullah; Azwir Azwir (TAQNIN: Jurnal Syariah dan Hukum, 2021)
Abstract: In general, the distribution of inheritance according to religion does not have problems because there are clear and firm arrangements both in the legislation and Islamic law itself, but problems will arise when it comes to the status of children, namely children born outside of legal marriage, religious law does not distinguish between legally legitimate children and legally illegitimate children as long as the child is not adulterous, but in Indonesian Islamic inheritance law it is certainly different, the case of such inheritance distribution in Langsa City is carried out with kinship where the legally valid child is willing to give their rights to their younger siblings who were born from their father's sirri marriage and thus the inheritance distribution system does not refer to the applicable laws and regulations.